The Advantages of Remote Work as an Efficient Form of Employment of Staff in Modern Conditions - Bondarenko Оlena M.; Rishko Yuliia I.; Tardaskina Tetyana M. (Bìznes Inform, 2018)
The article is aimed at researching the theoretical and practical aspects of organization kinds of remote work and considering its advantages as an efficient form of employment of staff. Information and communication technologies (ICTs) have a direct impact on the economy through the creation of new jobs and the transformation of the labor force. This transformation has led to a number of atypical forms of employment, one of which is remote work. The categories of employees who are most interested in the remote work form are provided. The advantages and disadvantages of remote work are analyzed for all interested parties: employers, employees, and the State. The emphasis is placed on the fact that, despite certain shortcomings, remote work is demanded and promising in view of tendencies in the development of the labor market.